Stimulus responsive cross-linked AIE-active polymeric nanoprobes: fabrication and biological imaging application. Issue 47 (13th October 2015) - Wan, Qing; Wang, Ke; He, Chengbin; Liu, Meiying; Zeng, Guangjian; Huang, Hongye; Deng, Fengjie; Zhang, Xiaoyong; Wei, Yen
Abstract : Stimuli responsive AIE-active polymeric luminescent nanoprobes have been fabricated through formation of dynamic bonds using AIE dye as the linker. Abstract : The combination of functional polymers and hydrophobic AIE dyes to prepare luminescent organic nanoparticles (LONs) with strong fluorescence, great water dispersibility and desirable biocompatibility has received a lot of attention for potential applications in cell imaging and theranostics. Although great effort has been devoted to preparing AIE dye based LONs through both covalent and noncovalent strategies, the fabrication of cross-linked AIE dye based LONs with stimulus responsive behavior has not been reported previously. In this work, the AIE dye based LONs were constructed via cross-linking aldehyde-containing polymers and AIE dye (2, 2′-diaminotetraphenyl ethylene) with two amino groups through formation of a Schiff base, which is a well-known dynamic bond with pH responsiveness. After successful incorporation of the hydrophobic AIE dye into the copolymers, cross-linked core–shell luminescent nanoparticles can be formed. The obtained AIE dye based LONs exhibited strong fluorescence and high water dispersibility because the AIE dye aggregated in the core and the hydrophilic polymers were covered on the shell. Biological evaluation results demonstrated that the AIE dye based LONs exhibited excellent biocompatibility and biological imaging properties. More importantly, these AIE dye based LONs exhibited desirable pH responsiveness, implying that these polymeric LONs can be potentially utilized for pH sensors and controlled drug delivery. With the combination of dynamic crosslinking and pH responsiveness, the obtained AIE dye based LONs should be of great significance for biomedical applications.